Human diamine oxidase is readily released from activated neutrophils ex vivo and in vivo but is rarely elevated in bacteremic patients. (September 2020) - Boehm, Thomas; Karer, Matthias; Matzneller, Peter; Buchtele, Nina; Ratzinger, Franz; Petroczi, Karin; Schoergenhofer, Christian; Schwameis, Michael; Burgmann, Heinz; Zeitlinger, Markus; Jilma, Bernd
During human diamine oxidase (DAO) ELISA development we noticed that in serum DAO concentrations appear to be higher when compared to plasma. Neutrophils contain DAO in the specific granules and we hypothesized that DAO is released from neutrophils during serum coagulation. If activation of neutrophils can release DAO, its concentrations might be elevated in vivo after lipopolysaccharide (LPS) administration and in bacteremic patients. Using blood from healthy volunteers DAO concentrations were measured ex vivo in serum, citrate, EDTA and heparin plasma over several hours and after activation of neutrophils. Lipopolysaccharide and granulocyte-colony stimulating factor (G-CSF) were administered to 15 and 8 healthy volunteers, respectively and DAO concentrations were measured at different timepoints. DAO antigen levels were also determined in three different subcohorts of patients with culture-proven bacteremia and high C-reactive protein (CRP) levels. DAO concentrations were elevated in a time-dependent manner in serum but not in EDTA or citrate plasma ( P  < 0.01). Neutrophil activation using phorbol myristate acetate (PMA) and zymosan dose-dependently caused DAO concentrations to be elevated more than 10-fold at both 22°C and 37°C (both P -values <0.001). Administration of LPS to healthy volunteers released DAO from neutrophils ( P  < 0.001). Of the 55 different bacteremic patients selected from three independent cohorts only 3 (5.4%) showed highly elevated DAO concentrations. Serum DAO concentrations do not accurately reflect circulating enzyme levels but coagulation-induced neutrophil activation and consequently DAO release. Only a few bacteremic patients show high DAO concentrations able to degrade histamine rapidly.